Liturgiese klere met besondere verwysing na die Nederduitsch Hervormde Kerk van Afrika - Beukes, M. J. du P. (Hervormde teologiese studies, 1993)
Liturgical clothes with special reference to the Nederduitsch Hervormde Kerk van Afrika In the Old Testament it was ruled that church officials should wear special clothes depicting the seperation between God and man. The function of the high priest was fulfilled by Jesus Christ and the gulf between God and man eliminated, making the need for liturgical dress unnecessary from the time of the New Testament. Since the earliest centuries of the church, official clothes for clergymen has been uncommon. Although the medieval Roman Catholic Church enforced official liturgical attire, the church reformists viewed such dress with scepticism. It is also considered that in the Hervormde Kerk no liturgical clothes should be worn, other than the academic robe as proof of competence.